The Use of NIHSS as an Assessment of Acute Stroke Severity - Imran, Yudhisman; Zahra, Ainaya Az (CoinReads Media Prima, 2024)
Stroke is a neurological emergency that is characterized by sudden neurological deficits caused by vascular injury (infarction, hemorrhage) in the brain. In Indonesia, stroke is the main cause of disability and mortality. The mortality rate of stroke patients is closely related to the severity of the stroke experienced by the patient. Therefore, a scoring system is needed to assess the severity of acute stroke. The National Institutes of Health Stroke Scale (NIHSS) is used as the gold standard for assessing stroke severity. NIHSS also helps the treatment plan of stroke patients and determine the patient’s prognosis. The use of NIHSS in assessing the severity of acute stroke deserves further attention because it has a significant impact on the outcome of stroke patients during the treatment period.